Morpho-agronomic characterization of sweet potato (Ipomoea batatas L.) accessions in dry Caribbean conditions (Colombia) - Gómez Delgado, Evelin; Morales Rebaza , Alfredo Francisco; Rosero Alpala, Elvia Amparo; Burbano Erazo, Esteban; Pastrana Vargas, Iván Javier (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2019)
The morphoagronomic characterization is very important to know the genetic diversity of collections of germplasm. The aim was characterizing the native Ipomoea batatas L. genetic resource collected in di erent regions of Colombia. Results allow knowing the level of variation of genotypes to be used in future breeding programs.